Developments of regional gross domestic product and the unemployment rate in Romania during 2000 - 2012 - Schonauer (Sacală) Corina (Computational Methods in Social Sciences, 2015)
Economic development of territorial units can be characterized by measuring the ability of producing goods and services and by measuring labor force in the area. The capacity of producing goods and services is measured by calculating the gross domestic product indicator. This article presents a comparative analysis of the evolution of regional GDP and the ILO unemployment rate at the level of the eight regions in Romania for a period of 13 years. The presented data come from the National Institute of Statistics of Romania.